Measuring community/environmental interventions: the Child Pedestrian Injury Prevention Project. Issue 1 (1st March 1999) - Stevenson, Mark; Iredell, Helena; Howat, Peter; Cross, Donna; Hall, Margaret
Abstract : Objectives —To assess the effectiveness of community/environmental interventions undertaken as part of the Child Pedestrian Injury Prevention Project (CPIPP). Setting —Three communities (local government areas) in the Perth metropolitan area, Western Australia. Methods —A quasiexperimental community intervention trial was undertaken over three years (1995–97). Three communities were assigned to either: a community/environmental road safety intervention and a school based road/pedestrian safety education program (intervention group 1); a school based road/pedestrian safety education program only (intervention group 2); or to no road safety intervention (comparison group). Quantification of the various road safety community/environmental activities undertaken in each community during the trial was measured, and a cumulative community activity index developed. Estimates of the volume and speed of vehicular traffic were monitored over a two year period. Results —Greater road safety activity was observed in intervention group 1 compared with the other groups. A significant reduction in the volume of traffic on local access roads was also observed over the period of the trial in intervention group 1, but not in the remaining groups. Conclusions —The findings indicate that the various community/environmental interventions initiated in collaboration with CPIPP in intervention group 1 contributed, in part, to the observed reduction in the volume of traffic. A combination of community/environmental interventions and education are likely to reduce the rate of childhood pedestrian injury.